Spatial numerical ranges of elements of subalgebras of C0(X) - Sin-Ei Takahasi (International Journal of Mathematics and Mathematical Sciences)
When A is a subalgebra of the commutative Banach algebra C0(X) of all continuous complex-valued functions on a locally compact Hausdorff space X, the spatial numerical range of element of A can be described in terms of positive measures.